Umbilical cord blood cell characteristics in very preterm neonates for autologous cell therapy of preterm-associated complications - Ren Zhuxiao; Han Jiangxue; Li Yongsheng; Pei Jingjun; Yang Shuo; Xu Fang; Zhang Qi; Zhang Shandan; Nie Chuan; Yang Jie (BMC, 2024)
Abstract Background There are emerging clinical evidence for umbilical cord blood mononuclear cells (UCBMNCs) intervention to improve preterm complications. The first critical step in cell therapy is to obtain high-quality cells. This retrospective study aimed to investigate the quantity and quality of UCBMNCs from very preterm infants (VPIs) for the purpose of autologous cell therapy in prevention and treatment of preterm complications. Methods Very preterm infants (VPIs) born in Guangdong Women and Children Hospital from January 1, 2017, to December 8, 2022, from whom cord blood was successfully collected and separated for public or private banking, were enrolled. The UCBMNCs characters from route cord blood tests performed in cord blood bank, impact of perinatal factors on UCBMNCs, the relationship between UCBMNCs characteristics and preterm outcomes, and the correlation of UCBMNCs characteristics and peripheral blood cells in VPIs were analyzed. Results Totally, 89 VPIs underwent UCB collection and processing successfully. The median cell number post processing was 2.6 × 108. To infuse a dose of 5 × 107 cells/kg, only 3.4% of infants required a volume of more than 20 mL/kg, which exceeded the maximum safe volume limit for VPIs. However, when infusing 10 × 107 cells/kg, 25.8% of infants required a volume of more than 20 ml/kg volume. Antenatal glucocorticoids use and preeclampsia was associated with lower original UCBMNCs concentration. Both CD34+ hematopoietic stem cells (HSC) frequency and colony forming unit - granulocyte and macrophage (CFU-GM) number correlated negatively with gestational age (GA). UCBMNCs characters had no significant effect on preterm outcomes, whereas a significant positive correlation was observed between UCBMNCs concentration and total white blood cell, neutrophil, lymphocyte and PLT counts in peripheral blood. Conclusion UCBMNCs collected from VPIs was feasible for autologous cell therapy in improving preterm complications. Setting the infusion dose of 5 × 107 cells/kg guaranteed a safe infusion volume in more than 95% of the targeted infants. UCBMNCs characters did not affect preterm complications; however, the effect of UCBMNCs concentration on peripheral blood classification count should be considered when evaluating the immunomodulation of UCBMNCs transfusion.